Social and behavioral research with end-users and healthcare providers into understanding perceptions of and reactions to a monthly oral contraceptive capsule in Bangladesh, Senegal and Zimbabwe - Moushira El-Sahn; Rose Elliott; Trisha Wood Santos; Mona El-Sahn; Jeff Lucas (Frontiers in Global Women's Health)
IntroductionUnintended pregnancy is a global public health challenge. Many contraceptive methods are available to end users, but non-use and discontinuation due to health concerns or side effects, particularly related to unpredictable or undesirable menstrual bleeding, are common. Oral contraceptive pills (OCPs) often have regular bleeding patterns compared to other hormonal contraceptives but require daily adherence. To address the issues of bleeding-related side effects and daily adherence, researchers are developing a monthly oral contraceptive (MOC) containing the same hormones as common OCPs. We studied women's and healthcare providers’ (HCPs’) perceptions of the MOC technology with the primary goal of providing feedback on product attributes to inform early design decisions.MethodsOur study consisted of a qualitative phase with in-person in-depth interviews (IDIs) with a total of 60 women of reproductive age in three regions in three countries (Bangladesh, Senegal, and Zimbabwe) and quantitative surveys, which took place after the qualitative phase, via face-to-face computer-assisted interviews of a total of 1,825 women in 17 regions in these three countries. We conducted 96 IDIs and 632 quantitative interviews with HCPs in one urban area per country.ResultsWomen's and HCPs’ perceptions of MOC product attributes were assessed and included a focus on potential menstrual changes and possible reasons for discontinuation. Overall, the most appealing attribute of an MOC was its 1-month duration. Women and HCPs alike preferred regular, monthly menstruation. Any unpredictable or irregular bleeding, including heavy bleeding or amenorrhea, would be a reason to discontinue an MOC if it were to have those attributes.DiscussionOverall, an MOC has a high and broad level of appeal amongst all the groups of women and HCPs who participated in the study and has a strong value proposition for important contraceptive needs including convenient duration, ease of use, discretion, and acceptable side effects. This appeal assumes that the experience of using an MOC would be very similar to that of daily OCPs except for dose timing. Future research on a hormonal MOC should include an exploration of women's tolerance and acceptability of potential side effects, particularly regarding bleeding, to validate its value proposition.